Daya Dukung Sumberdaya Air dan Indeks Kekritisan Air Sub DAS Cisokan Hulu - Dwi Rustam Kendarto; Edy Suryadi; Rizky Mulya Sampurno; Audi Putra Cahyabhuana (The University of Lampung, 2021)
Upper Cisokan sub-watershed is a natural ecosystem of water resource providers that can be used directly or indirectly by the community in it. The population rate and sectoral needs in a sub-watershed area are estimated have put pressure to the water resources balance. The value of the carrying capacity and the water criticality index in the existing condition and its projections for the next 10 years are known from the water balance analysis. The availability of water resources (Wn) was determined based on the flow rate probability (Q80) of Weibull Method, the value of groundwater estimation, springs and wells, and also the raw water supply of local water company. Water demand (qpt) was estimated based on Statistic data of Upper Cisokan sub-Watershed 2020 and the projection for 2030, industrial data, agricultural area data, livestock production data, and fishery area data. The water resources carrying capacity (Cw) of the Upper Cisokan sub-watershed is generally still adequate (High), but at the peak of the dry season, namely June to November, the water carrying capacity status shows a value of 1.84 (Critical) to 0.24 (Deficit). In general, the water criticality index is still safe (Not Critical), but in the dry period, especially in July, August and November, it shows a value of 125% to 421% (Very Critical). To anticipate the water crisis, all stakeholders should allocate water efficiently according to its availability. So that the sub-watershed ecosystem is sustainably provide ecosystem services for providing water resources to the community. Key words: Ecosystem Services, Water Supply, Water Demand, Water Balance, Water Resources Carrying Capacity, Water Criticality Index, Upper Cisokan Sub Watershed